Prognostic significance of TIM-3 expression pattern at diagnosis in patients with t(8;21) acute myeloid leukemia. Issue 1 (2nd January 2022) - Wang, Jun; Yang, Lu; Dao, Feng-Ting; Wang, Ya-Zhe; Chang, Yan; Xu, Nan; Chen, Wen-Min; Jiang, Qian; Jiang, Hao; Liu, Yan-Rong; Qin, Ya-Zhen
Abstract: Acute myeloid leukemia (AML) with t(8;21) is a heterogeneous disease and needs to be stratified. Both, cancer cells and immune cells participate in tumor initiation, growth and progression and might affect clinical outcomes. TIM-3 (T cell immunoglobulin and mucin domain-containing protein 3), an immune checkpoint molecule, is expressed not only on immune cells but also on leukemic stem cells (LSCs) in AML. This prompted us to investigate the prognostic significance of TIM-3 in t(8;21) AML. A total of 47 t(8;21) AML patients were tested for TIM-3 expression by multi-parameter flow cytometry at diagnosis. 35 of these, who received chemotherapy alone or along with allogeneic hematopoietic stem cell transplantation were followed up. The expression pattern of TIM-3 on T-cells and NK (natural killer) cells as a whole (T + NK) and LSCs were evaluated independently. High percentage of T + NK − TIM-3 + and CD34 + CD38 − TIM-3 + cells were significantly associated with a high 2-year cumulative incidence of relapse (CIR) ( p = 0.028, 0.016). Further, concurrent high frequencies of T + NK-TIM-3 + and CD34 + CD38 - TIM-3 + cells at diagnosis were significantly associated with a high 2-year CIR ( p < 0.0001) and this together with c-KIT D816 mutation were the independent adverse prognostic factors for relapse (hazard ratio (HR)=2.5, [95% confidence interval (CI), 1.1–6.0], p = 0.04; HR = 46.5, [95% CI, 2.7–811.5], p = 0.009). In conclusion, the expression pattern of TIM-3 on both T and NK cells and LSCs at diagnosis had prognostic significance in t (8;21) AML.